Liquidity, Activity, and Growth Influence Toward Profitability Performance with Leverage Variable and Cash Flow as Intervening Variable In Type â€œCâ€ Hospital at The PT Nusantara Sebelas Medika - Ainy Arga Astoety; Tri Ratnawati; Srie Hartutie Moehaditoyo (Media Ekonomi dan Manajemen, 2019)
The purpose of this study was to analyze financial ratios which included liquidity ratios, activity ratios, leverage ratios and profitability ratios to assess the financial performance of three type C hospitals managed by PT Nusantara Sebelas Medika. Data analyzed by Partial Least Square (PLS). The results in this study showed that Liquidity has insignificant effect on Leverage and cash flow. Activity also has insignificant effect on Leverage. Growth has insignificant on Cash Flow. Instead, growth was significant on leverage. Liquidity, activity and growth also have significant effect on profitability performance and support with positive influence direction in this study. Finally, leverage and cash flow have significant effect on profitability performance.